Antibacterial Activity of Abelmoschus manihot L. Leaf Extract Ointment Against Pseudomonas aeruginosa - Fani Lolyta Br Sihotang; Nerly Juli Pranita Simanjuntak; Razoki (PT Pustaka Cendekia Publisher, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from insulin resistance or deficiency. One of its severe complications is diabetic foot ulcers, which are prone to infection, especially by Pseudomonas aeruginosa—a Gram-negative opportunistic bacterium capable of forming biofilms and highly resistant to common antibiotics. This resistance complicates wound healing and increases the risk of amputation, emphasizing the need for alternative treatments. Abelmoschus manihot L. (Gedi leaves) contains bioactive compounds such as flavonoids, tannins, and phenolics, which are believed to possess antibacterial properties. This study aims to evaluate the potential of ethanolic Gedi leaf extract as an active ingredient in antibacterial ointment formulations. Ethanolic extracts were prepared and formulated into ointments at concentrations of 2%, 4%, 6%, and 8%. The formulations were tested for physical properties (pH, spreadability, organoleptic characteristics) and antibacterial activity against P. aeruginosa using the disk diffusion method. Results showed that the ointments had a uniform semi-solid texture, a characteristic herbal aroma, green color, and pH values ranging from 6.3 to 6.7—suitable for topical application. Spreadability ranged between 4.1 cm and 5.3 cm. The inhibition zones for the 2%, 4%, 6%, and 8% formulations were 6.67 mm, 8.00 mm, and 10.67 mm, respectively. No inhibition was observed with the negative control (DMSO), while the positive control (Bioplacenton) showed a 15.00 mm zone. In conclusion, Gedi leaf extract ointment demonstrated effective antibacterial activity against P. aeruginosa, with consistent physical properties across all concentrations. These findings suggest its potential as a natural topical therapy for treating bacterial infections in diabetic foot ulcers.